2008
DOI: 10.1007/s00704-008-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of relative drought indices in assessing climate-change impacts on drought conditions in Czechia

Abstract: The common versions (referred to as self-calibrated here) of the Standardized Precipitation Index (SPI) and the Palmer Drought Severity Index (PDSI) are calibrated and then applied to the same weather series. Therefore, the distribution of the index values is about the same for any weather series. We introduce here the relative SPI and PDSI, abbreviated as rSPI and rPDSI. These are calibrated using a reference weather series as a first step, which is then applied to the tested series. The reference series may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(145 citation statements)
references
References 40 publications
1
143
0
1
Order By: Relevance
“…Although precipitation is the main variable explaining the frequency, duration and severity of 286 droughts (Chang and Cleopa, 1991;Heim, 2002), recent studies have shown that the effect of 287 temperature (or evapotranspiration) is significant (Hu and Willson, 2000), particularly under global 288 warming scenarios (Dubrovsky et al, 2008). Abramopoulos et al (1988) showed that evaporation 289 and transpiration can consume up to 80% of rainfall, and found that the efficiency of drying due to 290 temperature anomalies is as high as that due to rainfall shortage.…”
Section: Hydrological Drought Index Calculation 185 186mentioning
confidence: 99%
“…Although precipitation is the main variable explaining the frequency, duration and severity of 286 droughts (Chang and Cleopa, 1991;Heim, 2002), recent studies have shown that the effect of 287 temperature (or evapotranspiration) is significant (Hu and Willson, 2000), particularly under global 288 warming scenarios (Dubrovsky et al, 2008). Abramopoulos et al (1988) showed that evaporation 289 and transpiration can consume up to 80% of rainfall, and found that the efficiency of drying due to 290 temperature anomalies is as high as that due to rainfall shortage.…”
Section: Hydrological Drought Index Calculation 185 186mentioning
confidence: 99%
“…In this research, the self-calibrated SPI (scSPI) was used for the Czech drought conditions. Being inspired by Dubrovsky et al (2008), we applied a similar original algorithm to calculate SPI for a single reference station or an aggregated SPI for all stations (in our case Zatec and 56 aggregate stations). For more details regarding the methodology, see Dubrovsky et al (2008).…”
Section: Standardized Precipitation Indexmentioning
confidence: 99%
“…Being inspired by Dubrovsky et al (2008), we applied a similar original algorithm to calculate SPI for a single reference station or an aggregated SPI for all stations (in our case Zatec and 56 aggregate stations). For more details regarding the methodology, see Dubrovsky et al (2008). The present version of SPI uses a gamma distribution whose parameters are estimated separately for each of the 6 months of the warm period and/or values for different time scales: 1, 2, 3, and 6 months.…”
Section: Standardized Precipitation Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…These conditions inversely affect both the natural vegetation and the agriculture of the region as well as the water resources. Severe and extremely dry conditions result in irrigation cutbacks, overexploitation of groundwater and significant losses of crop yields [19]. In Greece, especially in Central Thessaly, the major methodological drawback for a long-term assessment of regional climate and its variability results from the lack of suitable observations or simulated data.…”
Section: Study Area and Data Basementioning
confidence: 99%